Chong Sport Trading E-Commerce Website - Ahmad Danial Azmi; Hasan Basari, Abd Samad (Applied Information Technology And Computer Science, 2025)
Despite the widespread adoption of e-commerce, many small and medium-sized enterprises (SMEs) in this industry struggle to establish a robust online presence, resulting in limited market reach and growth potential. This project addresses the gap by developing a comprehensive e-commerce platform tailored for Chong Sport Trading, a local SME specializing in premium sports equipment. The main objective of this research is to design and implement an intuitive, user-friendly, and feature-rich e-commerce website that caters to both general and niche audiences in the sports market. The methodology includes Agile software development, employing iterative design, coding, and testing phases to ensure user-centricity and adaptability. The results show a big improvement in user engagement and sales efficiency, with early prototypes getting great feedback for being easy to use and highly functional. The project highlights the importance of digital innovation in empowering SMEs to compete in a highly saturated market. Future work will focus on enhancing scalability, integrating AI-driven analytics for customer insights, and expanding the platform's ecosystem to include mobile applications. This research contributes to the digital transformation of SMEs and sets a foundation for further exploration in e-commerce platform development.